What is osteoporosis? - Christodoulou, C; Cooper, C (2003)
Osteoporosis is a very common disorder, which results in an increase in fracture risk. The annual cost attributable to hip, vertebral, and wrist fractures in England and Wales is pound 1.7 billion. Significant mortality and morbidity are associated with osteoporotic fractures. The method that is most widely used for the diagnosis of osteoporosis is dual energy x-ray absorptiometry. The aim of prevention and treatment of osteoporosis is to prevent the occurrence of future fractures. Lifestyle changes should be encouraged in high risk patients. Pharmacological treatments include the bisphosphonates, hormone replacement therapy, selective oestrogen receptor modulators, calcitonin, the 1-34 fragment of parathyroid hormone, calcium and vitamin D supplements, and calcitriol.